2001
DOI: 10.1162/108819801753358526
|View full text |Cite
|
Sign up to set email alerts
|

Does It Really Pay to Be Green? An Empirical Study of Firm Environmental and Financial Performance: An Empirical Study of Firm Environmental and Financial Performance

Abstract: Summary Previous empirical work suggests that firms with high environmental performance tend to be profitable, but questions persist about the nature of the relationship. Does stronger environmental performance really lead to better financial performance, or is the observed relationship the outcome of some other underlying firm attribute? Does it pay to have cleanrunning facilities or to have facilities in relatively clean industries? To explore these questions, we analyze 652 U.S. manufacturing firms over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
568
1
22

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 894 publications
(648 citation statements)
references
References 26 publications
31
568
1
22
Order By: Relevance
“…As several authors have pointed out (King andLenox 2001, Reinhardt 1999), the most relevant question is presumably not "does it pay to be green", but rather when and for whom may it pay to be green.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As several authors have pointed out (King andLenox 2001, Reinhardt 1999), the most relevant question is presumably not "does it pay to be green", but rather when and for whom may it pay to be green.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of measures have been employed in previous studies of the relationship between environmental and economic performance. Among the more objective measures, percentage change in emissions of an aggregate of pollutants (Hart andAhuja 1996, King andLenox 2001) or an index of emissions of various pollutants (Jaggi andFreedman 1992, Wagner et al 2002) are some of the most frequently applied ones. Of course, none of these measures are fully satisfactory, and they may capture different aspects of environmental performance.…”
Section: Measure Of Environmental Performance (Enp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have established that the relationship between CSP and CFP cannot be proved due to the complex relationship between company and society (Lorraine, Collison, and Power, 2004;King and Lenox, 2001;Murray, Sinclair, Power, and Gray, 2006).…”
Section: The Relationship Between Csp-cfpmentioning
confidence: 99%
“…Business policies nowadays have a dedicated section for environment management practices. The approach from purely looking for the economic profit is shifting towards profound management strategies (King et al, 2001). Tilley (2000) observed that instead of sector specific procedures and guidelines, the SMEs only have general information on the environment subject.…”
Section: Introductionmentioning
confidence: 99%